Vận dụng Lí thuyết giáo dục toán học gắn với thực tiễn (RME) trong dạy học nội dung “Hình hộp chữ nhật và hình lập phương” (Toán 5) - Lê, Thị Bình Nguyên; Nguyễn, Anh Tuấn (Tạp chí Giáo dục, 2025)
The 2018 General Education Mathematics Program emphasizes the application of mathematics in practice and the connection between mathematics and practice. Realistic Mathematics Education (RME) is a theory designed based on two core views: mathematics must be linked to practice and mathematics is a human activity. Applying RME theory to teaching mathematics is consistent with the viewpoint of modern education. The study proposes a teaching process for the content “Rectangular box, cube” (Math 5) and illustrates this process in teaching. Teachers need to have an understanding of the core principles of RME; be able to build experiential situations, practical problems and open-ended questions to guide students to build mathematical problems and discover knowledge on their own.